Practices of Marketing Strategies in Promotion of Women Entrepreneurs in Manipur - Singh, N. Tejmani; Singh, P. Chinglen (Journal of Commerce and Trade, 2012)
Women entrepreneurs have started taking leading roles in the country’s economic development. One of the remarkable observations of today is entry of ‘Women’ into the entrepreneurial ventures. There has been a shift in the empowerment of women in India. Even though, in the past, they were treated inferior to their male counterpart, now they have come forward with increasing interest and vigour to be the entrepreneurs. They have started extending their productive hands in taking leading roles in the enterprise promotion along with their usual households. Again, Government’s initiation through certain policies changes in their favour has accelerated the promotion and growth of women entrepreneurship in India. The case studies to be cited in paper highlights the entrepreneurial abilities of women today. One of the remarkable observations is that the present women entrepreneurs have become more customer friendly, and have clear understanding of the philosophy of marketing. Accordingly they have been adopting strategic marketing in real practice in success of their enterprise. This adoption of strategic marketing practice has made them to be successful women entrepreneurs. The specific contribution of marketing in the organization lies in the formulation of strategies to choose the right customer, build relationships of trust with them and create a competitive advantage. This paper is an attempt to presents the trend and constraints of the growth of women entrepreneurship and focuses on the understanding and adoption of strategic marketing by them in managing their enterprises. This has been discussed through the case study.